New insights into natural products that target the gut microbiota: Effects on the prevention and treatment of colorectal cancer - Lu, Lu; Dong, Jiahuan; Liu, Yujing; Qian, Yufan; Zhang, Guangtao; Zhou, Wenjun; Zhao, Aiguang; Ji, Guang; Xu, Hanchen (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is one of the most common malignant carcinomas. CRC is characterized by asymptomatic onset, and most patients are already in the middle and advanced stages of disease when they are diagnosed. Inflammatory bowel disease (IBD) and the inflammatory-cancer transformation of advanced colorectal adenoma are the main causes of CRC. There is an urgent need for effective prevention and intervention strategies for CRC. In recent years, rapid research progress has increased our understanding of gut microbiota. Meanwhile, with the deepening of research on the pathogenesis of colorectal cancer, gut microbiota has been confirmed to play a direct role in the occurrence and treatment of colorectal cancer. Strategies to regulate the gut microbiota have potential value for application in the prevention and treatment of CRC. Regulation of gut microbiota is one of the important ways for natural products to exert pharmacological effects, especially in the treatment of metabolic diseases and tumours. This review summarizes the role of gut microbiota in colorectal tumorigenesis and the mechanism by which natural products reduce tumorigenesis and improve therapeutic response. We point out that the regulation of gut microbiota by natural products may serve as a potential means of treatment and prevention of CRC.